Embolization of pulmonary sequestration with Onyx: an unusual application - Alper Hazım Gürsu; Fatih Boyvat; Birgül Varan; İlkay Erdoğan (KARE Publishing, 2014)
We report a baby with intralobar pulmonary sequestration who was successfully treated with a new embolization agent, Onyx. A 1.5-month-old female infant was admitted to our hospital with sweating and fatigue. Telecardiography showed cardiomegaly, dextrocardia, and increased pulmonary vascular markings. In thoracic computerized tomography, pulmonary sequestration, right pulmonary hypoplasia, and large collateral arteries were seen. The collateral arteries were originating from the celiac trunk and aorta. Echocardiography revealed enlargement of the left atrium and ventricle and left ventricle systolic dysfunction. Angiography revealed a large feeding artery and three branches originating from the aorta and another feeding artery originating from the celiac trunk. We performed embolization of the feeding arteries and their branches, with coils and Onyx. The procedure was performed without complications, and all feeding arteries were completely occluded. The infant started to gain weight. One year later, the infant's body weight had increased and she had no respiratory problems or signs of congestive heart failure. In this case report, we suggest that embolization with Onyx is a reliable alternative method to surgery for infants with pulmonary sequestration. With future studies, pulmonary sequestration embolization with Onyx may become an acceptable and easy treatment option in pediatric patients.